Identifying the depreciation rate of durables from marginal spending responses - Jin Cao; Chao Cui; Valeriya Dinger; Martin Blomhoff Holm; Shulong Kang (Norges Bank, 2022)
This paper presents a novel method to estimate the depreciation rate of durable goods using a combination of identified marginal and average spending shares. We apply our method to Chinese spending responses to disposable income changes induced by monetary policy in 2008-2009. The marginal spending response is 0.40. Durable goods make up about 45% of this marginal spending response. By combining this marginal spending share on durables with an average spending share of 14%, we estimate the annual depreciation rate of durables in China to be 0.16.
hdl:11250/2978669
Keywords: E21; E52; 330; Consumption; Durables; Monetary Policy